Three-dimensional stability analysis of maxillomandibular advancement surgery with and without articular disc repositioning - Bianchi, Jonas; Porciúncula, Guilherme Machado; Koerich, Leonardo; Ignácio, Jaqueline; Wolford, Larry Miller; Gonçalves, João Roberto (Journal of cranio-maxillo-facial surgery, 2018)
This retrospective cohort study aimed to assess, three-dimensionally, mandible and maxilla changes following maxillomandibular advancement (MMA), with and without repositioning of TMJ articular discs. The sample comprised cone-beam computed tomography data from 32 subjects: group 1 (n = 12) without disc displacement and group 2 (n = 20) with bilateral disc repositioning. An automatic cranial base superimposition method was used to register the images at three time points: T1 (preoperative), T2 (postoperative), and T3 (at least 11 months follow-up). To assess surgical changes (T2–T1) and adaptive responses (T3–T2), the images were compared quantitatively and qualitatively using the shape correspondence method. The results showed that surgical displacements were similar in both groups for all the regions of interest except the condyles, which moved in opposite directions — group 1 to superior and posterior positions, and group 2 to inferior and anterior positions. For adaptive responses, we observed high individual variability, with lower variability in group 2. Sagittal relapse was similar in both groups. In conclusion, there were no significant differences in skeletal stability between the two groups. The maxillomandibular advancement surgeries, with rotation of the occlusal plane, had stable results for both groups immediately after surgery and at 1-year follow-up. •The skeletal changes following maxillomandibular advancement with and without repositioning of TMJ articular discs were stable at long-term follow-up.•The presence of discs in their normal positions did not prevent the condyles from moving towards the superior and posterior positions, showing an additional load on the TMJs.•Patients who received concomitant TMJ surgery had the condyles moved towards the inferior and anterior positions, due to the space created for disc repositioning.